Performing Worldly Works in The Mosque: A Contemporary Jurisprudence Study - Kamal Sadiq Yasin (QALAAI ZANIST JOURNAL, 2020)
It is known that the first work of the Prophet –peace be upon him- when he arrived to Madinah is building a mosque, so the mosque is a place of worship, performing Islamic rituals such as prayer, reading the noble Qur’an, remembrance of Allah the Almighty. It is also a school to learn beautiful morals. the mosque, in the Prophet’s era, was a place for giving scientific and educational lessons, speeches, sermons, consultations, and taking decisions. In the mosque, the prophet-peace be upon him- used to receive delegations, conclude covenants. It was a council of judiciary to resolve the types of disputes between members of society, and many worldly matters are practiced in it. Hence, this research came to study the rule of some contemporary issues that practiced in the mosque in Islamic jurisprudence perspective, highlighting the scholars’ sayings on this topic. It also examines the evidence of scholars from the Qur’anic verses, prophetic traditions, and the narrations of the Companions and the followers, with other evidences such as consensus and analogy..etc, with the discussion of evidences. The research clarifies the correct statement in the issues. It is divided into an introduction, a preamble, fourteen sections, and a conclusion in which the researcher shows the most important results that he reached.